2005
DOI: 10.1080/00288330.2005.9517375
|View full text |Cite
|
Sign up to set email alerts
|

Relative sensitivities of common freshwater fish and invertebrates to acute hypoxia

Abstract: The acute lethality of low dissolved oxygen (DO) was examined in laboratory studies using several New Zealand freshwater fish and two invertebrates at 15°C. The 48-h LC50 value was used as the endpoint for acute DO sensitivity as, owing to rapid mortality, this was found to best approximate the threshold lethal concentration. Median lethal time to death did not provide a reliable endpoint for comparing sensitivities. Fish LC 50 values varied from 0.54 to 2.65 mg litre -1 , with inanga whitebait (Galaxias macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 29 publications
7
52
0
3
Order By: Relevance
“…This could be due to the increased C: N ratio which stimulates the growth of the heterotrophic bacteria which in turn require oxygen for their growth. This finding is in accordance with that of Landman et al [44] who determined the hypoxia sensitivity of ten fish and invertebrate species in plastic aquaria in New Zealand and found that there was a decrease in dissolved oxygen concentrations with the increase of C: N ratio. Sun et al [45] studied the supplementation and consumption of dissolved oxygen and their seasonal variations in a shrimp pond.…”
Section: Dissolved Oxygen (Do)supporting
confidence: 82%
“…This could be due to the increased C: N ratio which stimulates the growth of the heterotrophic bacteria which in turn require oxygen for their growth. This finding is in accordance with that of Landman et al [44] who determined the hypoxia sensitivity of ten fish and invertebrate species in plastic aquaria in New Zealand and found that there was a decrease in dissolved oxygen concentrations with the increase of C: N ratio. Sun et al [45] studied the supplementation and consumption of dissolved oxygen and their seasonal variations in a shrimp pond.…”
Section: Dissolved Oxygen (Do)supporting
confidence: 82%
“…This variability, sometimes ranging from anoxic to supersaturated over a single day, means that dissolved oxygen at the time of sampling may not reflect the conditions that the invertebrate community recently experienced. It has been established that dissolved oxygen concentration can alter animal behaviour through avoidance (Levin et al 2009), feeding cessation (Nestlerode and Diaz 1998;Riedel et al 2014), reduction in activity (Riedel et al 2014), and death (Miller et al 2002;Nedergaard et al 2002;Landman et al 2005;Howarth 2008). Previous work by in this region showed evidence of short-term response to sustained hypoxia by amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…Metrics were based on work by Coffin et al (submitted), which found that hypoxia (proportion of time below 4 mg/L), dissolved oxygen supersaturation (proportion of time above 10 mg/L), and the coefficient of variation of dissolved oxygen were all predicted by water residence time and nitrate loading. Additionally, metrics for the proportion of time <2 mg/L, <6 mg/L, and >15 mg/L were incorporated for greater resolution of sites that were minimally and maximally impacted by nutrients (Miller et al 2002;Landman et al 2005;Riedel et al 2014;Coffin et al submitted). The duration of 48 h was selected because effects from hypoxia prior to invertebrate sampling would likely still be evident , and although not investigated directly in this manuscript, the impacts on behaviour and survivorship can occur after extended exposure to hypoxia (Miller et al 2002;Riedel et al 2014).…”
Section: Water Chemistry and Dissolved Oxygenmentioning
confidence: 99%
“…low velocity and discharge). Crayfish tend to be more tolerant of low water quality than most North American stream fish (Seiler and Turner, 2004;Landman et al, 2005), and in our study, crayfish occurred at several sites with relatively low DO. Moreover, some crayfish burrow into mud to survive periods of drought (Jordan et al, 2000), whereas fish of this region cannot survive in dry streambeds.…”
Section: Species-environment Relationshipsmentioning
confidence: 90%
“…Relationships between species abundance, richness, and composition with water depth, dissolved oxygen (DO) concentration, substrate composition and other environmental factors have been described in many systems (Schlosser, 1987;Chipps et al, 1994;Landman et al, 2005). Furthermore, several recent studies have revealed the relative influence of local and regional environmental factors on community structure of aquatic macrofauna (Hugueny and Paugy, 1995;Marsh-Matthews and Matthews, 2000;Jackson et al, 2001).…”
Section: Macrofauna As An Ecological Indicatormentioning
confidence: 97%